Dual genetic diagnoses: Atypical hand‐foot‐genital syndrome and developmental delay due to de novo mutations in HOXA13 and NRXN1. Issue 3 (21st November 2015) - Wallis, Mathew; Tsurusaki, Yoshinori; Burgess, Trent; Borzi, Peter; Matsumoto, Naomichi; Miyake, Noriko; True, Deanna; Patel, Chirag
Abstract : We describe a male patient with dual genetic diagnoses of atypical hand‐foot‐genital syndrome (HFGS) and developmental delay. The proband had features of HFGS that included bilateral vesicoureteric junction obstruction with ectopic ureters, brachydactyly of various fingers and toes, hypoplastic thenar eminences, and absent nails on both 4th toes and right 5th toe. The atypical features of HFGS present were bilateral hallux valgus malformations and bilateral preaxial polydactyly of the hands. Chromosomal microarray analysis identified a de novo 0.5 Mb deletion at 2p16.3, including the first four exons of the NRXN1 gene. Whole exome sequencing and subsequent Sanger sequencing identified a de novo missense mutation (c.1123G>T, p.Val375Phe) in exon 2 of the HOXA13 gene, predicted to be damaging and located in the homeobox domain. The intragenic NRXN1 deletion is thought to explain his developmental delay via a separate genetic mechanism. © 2015 Wiley Periodicals, Inc.